A Comparison of Piaffe in Competition with the Fei Definition of the Movement. (June 2014) - Moore, G; Nankervis, K; Dumbell, L; Douglas, J
Abstract : Introduction: Requirements of competitive dressage should be reviewed periodically to inform training of horses and judges. The aim of this study was to determine whether features of the FEI definition of piaffe are achieved in competition and to correlate the judges′ scores with the degree of conformity to the definition. Methods: Videography (60 Hz) of 3 piaffe strides (performed at marker D within a field of view 6 x 4 m) from 60 Grand Prix horses was used to measure croup height (CH), poll height (PH), the highest point of the neck (PN), peak height of the fore (FTpeak) and hindlimb toe (HTpeak), the level of a point half way down the cannon (MC) and the level of the fetlock joint (FJ) to within ± 0.01 m. Paired t‐tests were used to compare CH in piaffe with that in halt, PH with PN, FTpeak with MC and HTpeak with FJ during piaffe to determine if the criteria within the definition were met. Piaffe scores from 5 judges were obtained from a subset of 17 horses. Results: CH was higher in piaffe than in halt (P<0.001). PN was higher than PH in piaffe (P = 0.001). FTpeak was lower than MC (P = 0.001) and HTpeak was lower than FJ (P = 0.001). There was no significant difference (P = 0.836) between the scores awarded to each horse but also no correlation between the scores and PH (P = 0.331), CH (P = 0.829), FTpeak (P = 0.784) or HTpeak (P = 0.924). Conclusions: Piaffe performed in competition does not conform to the FEI definition of the movement although judges′ scores appear consistent. This finding suggests that the definition of the movement or judge training should be reviewed. Ethical Animal Research: Project approved by Hartpury College Research Ethics Committee. Explicit owner informed consent for participation in this study is not stated.Sources of funding:  Hartpury College.Competing interests:  none.